Recent Advances in Earth‐Abundant Heterogeneous Electrocatalysts for Photoelectrochemical Water Splitting. Issue 6 (11th April 2017) - Hou, Yang; Zhuang, Xiaodong; Feng, Xinliang
Abstract : Photoelectrochemical (PEC) water splitting has been considered as the most promising strategy to obtain hydrogen fuels and oxygen. Developing earth‐abundant heterogeneous electrocatalysts with high catalytic activity and stability is of great importance for achieving highly efficient water splitting. Here, an overview of the recent developments in the earth‐abundant heterogeneous electrocatalysts for PEC water splitting is presented. The main earth‐abundant electrocatalysts for the PEC hydrogen‐evolution reaction (PEC‐HER) include transition‐metal dichalcogenide (TMD)‐based materials, transition‐metal carbides/phosphatides, and N‐doped graphene, whereas the earth‐abundant PEC oxygen‐evolution reaction (PEC‐OER) electrocatalysts are focused on mixed transition‐metal oxides, TMD‐based materials, and transition‐metal‐ and/or heteroatom‐doped carbon catalysts. In addition, earth‐abundant bifunctional (HER/OER) electrocatalysts, including NiFe layered double hydroxide and Co–Mn oxide nanoparticles/nitrogen‐doped carbon frameworks, are introduced for overall water splitting. The strategies for improvement of the catalytic performance and the composition/structure–catalytic‐activity relationships are highlighted. Finally, current existing challenges and the future research directions for enhancing the PEC water‐splitting performance of earth‐abundant heterogeneous electrocatalysts are provided. Abstract : Water electrolysis is an efficient and attractive strategy to obtain hydrogen fuels and oxygen with high purity. Recent progress regarding earth‐abundant heterogeneous electrocatalysts as substitutes for precious‐metal‐based catalysts in photoelectrochemical water splitting is reviewed. Composition/structure–activity relationships are highlighted, and perspectives on challenges and opportunities for enhancing the photoelectrochemical water‐splitting performance are discussed.